Capability of HYDRUS wetland module to simulate flow and nitrogen removal processes in pilot-scale treatment peatlands under frost and no-frost conditions - Khan, Uzair Akbar; Postila, Heini; Kujala, Katharina; Heiderscheidt, Elisangela; Ronkanen, Anna-Kaisa (Elsevier, 2022)
The HYDRUS wetland module is widely used together with the biokinetic model CWM1 to simulate reactive transport of contaminants in constructed wetlands. However, this approach has not been used previously to simulate processes in peat-based wetlands operating in cold climates and treating mining-influenced water. In this study, the goal was to clarify changes in flow, transport, and nitrogen removal processes in cold climate treatment peatlands by assessing the performance of HYDRUS-CWM1. Flow and non-reactive transport of tracer, and reactive transport of ammonium, nitrite, and nitrate, in two pilot wetlands operated under controlled conditions representing frozen (winter) and frost-free (summer) periods were simulated. Model simulation outputs were compared against data obtained from the pilot wetlands and from a full-scale treatment peatland treating mining-influenced water in an Arctic region. Initial peaks in tracer concentration were simulated satisfactorily, but transformation and transport of nitrogen species in treatment peatlands, especially under partially frozen conditions, were modeled with only limited success. Limitations of the model and the assumptions made for the simulations have been discussed to highlight the challenges in modeling of treatment peatlands. Highlights • Initial peaks in tracer concentration were simulated satisfactorily. • Transport of nitrogen especially in winter was modeled with limited success. • Limitations of the model and possibilities for improvement are discussed. • Possibility to use multiple HYDRUS add-ons simultaneously may be critical.